(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Children between 1-5 years constitute 13.59% of Indian population. The children from this age group constitute an important valuable segment of population from the nutritional standpoint. The problems of infection and malnutrition are most prevalent in this age group. The rural area of Muzaffarpur has been facing this problem last few years. It is urgent need to reduce the level of malnutrition and micronutrient deficiency among children, as it acts as a contributory factor for the development of disease, because the state of malnutrition in Muzaffarpur, District, a large segment of its population is suffering from various nutritional disorder. Every second child under the age of 5 years in Muzaffarpur district of Bihar is stunted. Between 2016, 2018 at approximately 228 cases of AES were reported and 161 death due to this disease in 2019 in Muzaffarpur district. Claiming WHO, Unicef Report. It is urgent to reduce the level of micro and macro nutrient deficiency among children. One of the best solutions for this nutritional problems to encourage the proper nutritional education and strategies for improving physics access to food materials.